A novel species of Phaeoisaria (Pleurotheciaceae, Sordariomycetes) from the Tibetan Plateau, China - Xu, Ke; Xu, Rong-Ju; Li, Jia-Ning; Zhao, Qi; Zhu, Ying-An (Phytotaxa, 2024)
Phaeoisaria is widely distributed in the Northern Hemisphere and characterized by straight or flexuous, erect, dark brown to black synnemata with parallelly adpressed conidiophores and ellipsoidal to obovoid, solitary, hyaline, aseptate, acrogenous conidia. This study’s phylogenetic analyses of combined ITS, LSU, and SSU sequence data showed that the eight Xizang Phaeoisaria strains represent at least three phylogenetic species. A new species Phaeoisaria motuoensis, and two new geographical records of P. clematidis and P. sedimenticola from Xizang, China are reported. The taxa are introduced here with descriptions, color photographs, and phylogenetic analyses results and are compared with similar species.